Development of games-based mobile learning model to teach arithmetic at an elementary school in Saudi Arabia - Alkhaldi, Ibrahim Abdulrahman I (2021)
Mathematics teaching and learning is an essential component of the modern educational system. Despite its immense significance, Saudi primary and secondary schools' performance in mathematics has been notably underwhelming. The aim of this study therefore was to design and develop a teaching model that is based on activities for the teaching of arithmetic at the elementary school level. The study was based on Design and Development Research (DDR) proposed by Richey and Klein (2007, 2013) which consists of three phases. Under the Phase 1, needs analysis was conducted through qualitative semi-structured interviews with 16 elementary mathematics teachers particularly teaching under the Saudi system of education. The data collected for the three phases were analysed through thematic analysis and fuzzy Delphi methods. The fuzzy Delphi involved the calculation of the threshold value, ‘d’ in order to establish experts’ consensus on all questionnaire items. In addition, defuzzification values were also generated in order to establish experts’ agreement. In accordance with the three phases, the findings of Phase 1 indicated that the elementary mathematics teachers opined that there are problems with the current methods employed in teaching arithmetic at the elementary school level and that employing technology in the form games-based mobile learning will solve issues and problems currently faced in teaching arithmetic at the elementary school level. Phase 2 findings were based on what was gathered from the experts during the NGT sessions that led to the finalization, prioritization and the ranking of the teaching activities. The findings also led to the classification of the activities into four domains, namely introductory domain, contents domain, technology domain, and evaluation domain. As for the findings of FDM Phase 2, the experts reached an overall consensual agreement (d = 93.5) regarding their views on the selected teaching activities (Amax12.867), experts’ views on the classification of the teaching activities (Amax13.200), experts’ views on the teaching activities under the introductory domain (Amax12.733), experts’ views on activities classified as contents domain (Amax13.133), experts’ views on the activities classified as technology domain (Amax 12.733), experts’ views on the activities classified as evaluation domain (Amax 13.133). Similarly, the experts who participated at the evaluation phase also consensually reached an agreement among them (d = 93.4). The findings showed that the defuzzification value obtained exceeded the minimum value of 10.5 with the experts' agreement on the domain classification of games-based mobile learning of the obtaining the average defuzzification value (Amax13.100) more than the minimum value of 10.5. The findings of the second aspect of the evaluation questionnaire indicated that the average defuzzification value obtained by the items was (Amax13.126) also more than the minimum value of 10.5. Findings of the study have some far-reaching implications which include the use of both formal classroom teaching and informal learning to help students achieve their learning objectives. In addition, by combining the all the theories adopted and methodological choices made by this study, the findings also have some theoretical and methodological implications including combining all different methodological choices in achieving the study's objectives.